Penggunaan Material Mycelium dalam Perancangan Kembali Microlibrary Warak Kayu - Farhah Amira Fonna; Diva Iryanti Irsyad; Kaylila Fathia Adriansyah; Labitta Qonitah; Mochamad Donny Koerniawan (Universitas Sebelas Maret Surakarta, 2023)
Mycelium composites are emerging as a new sustainable. Mycelium is a fungi that is produced from the remains organisms and can be used as a natural adhesive to unite and grow in a biomass. By responding to a critical evaluation of SHAU Indonesia's Warak Kayu Microlibrary, this paper aims to explore and develop bio-design in the use of mycelium as a sustainable alternative to architectural elements. In this paper, agricultural waste such as coffee grounds and wood will be used as substrates in the formation of mycelium composites. . The method used in this research is descriptive qualitative methods with data collection derived from literature studies and followed by data analysis. From this paper, it is found that mycelium can be used as an architectural element in the form of facade panels that pay attention to audial comfort by utilizing agricultural waste as nutrients for mycelium to be processed into a material.